THE UNITED STATES’ INVOLVEMENT IN THE IRAN-ISRAEL CONFLICT: A NORMATIVE ANALYSIS OF NEUTRALITY AND COLLECTIVE DEFENSE UNDER INTERNATIONAL LAW - Domingos Correia Tavares; Budi Parmono; Rahmatul Hidayati (Pena Cendekia Insani, 2025)
This research focuses on analyzing the United States' involvement in the conflict between Iran and Israel through the provision of military aid to Israel, as well as its implications for the principles of neutrality, collective defense, and the laws of war from an international legal perspective. This study uses a normative qualitative research method with a juridical-analytical approach to various international legal instruments, such as the Hague Convention, the United Nations Charter, and the doctrines of jus ad bellum and jus in bello. The results of the study indicate that the form of strategic support from the United States, which includes the supply of defense equipment and intelligence collaboration, not only exceeds the boundaries of the principle of neutrality but also exploits the principle of collective defense unilaterally without formal legitimacy from the UN Security Council. Furthermore, this involvement contributes to violations of international humanitarian law, particularly in the context of proportionality and the protection of civilians. The implications of this research indicate the need to reinterpret and strengthen oversight mechanisms regarding the practice of third-state intervention in armed conflicts, in order to prevent the delegitimization of international law and maintain stability and justice in the global system.